Online Banking Service Practices and Its Impact on E-Customer Satisfaction and E-Customer Loyalty in Developing Country of South Asia-Nepal - Dhruba Kumar Gautam; Gunja Kumari Sah (SAGE Open, 2023)
The aim of this paper is to investigate the association and impact between online banking service practices on e-customer satisfaction, and e-customer loyalty. In addition, it aims to analyze mediating role of e-satisfaction to online banking service practices and e-loyalty. The research followed the E-S-QUAL model to measure the online banking service quality (OBSQL) by five dimensions: e-customer service, site of the organization, website efficiency, user-friendliness, security, and privacy. It is based on quantitative research approach with a structured questionnaire through primary data collection by stratified random sampling. Out of 475 questionnaires distributed, 384 usable questionnaires were used, and SPSS and AMOS were used to analyze. An exploratory factor analysis was used to confirm the online banking service quality dimensions and structural equation modeling was employed to estimate the parameters and structure. The result explained that the efficiency of the website and e-customer service were highly influential dimensions of online banking service practices, followed by user-friendliness, security and privacy, and the organization’s site. E-customer satisfaction significantly influences e-customer loyalty, and e-satisfaction mediates the association between online banking services and e-customer loyalty, which is a prime concern to bankers, users, and policymakers for continuous development. This research presents a model to recognize the quality of online banking services that affects electronic customer loyalty and satisfaction in developing countries of South Asia.